KOMUNIKASI TRANSENDENTAL NYENUK DALAM UPACARA NGENTEG LINGGIH DI PURA DESA, DESA PELAGA, KECAMATAN PETANG, KABUPATEN BADUNG - I WAYAN RUSDIKA; I Wayan Wastawa; I Wayan Sukabawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Nyenuk transcendental communication is a series of ngenteg linggih ceremonies carried out by the community after the construction or restoration of the temple, as carried out by the Pelaga Indigenous Village community. The fun procession with sacred dialogue as a tangible form of transcendental communication shows its own uniqueness. 1) What is the form of transcendental communication in the ngenteg linggih ceremony?, 2) What is the function of transcendental communication in the ngenteg linggih ceremony?, 3) What is the meaning of the transcendental communication of nyenuk in the ngenteg linggih ceremony? The theories used to analyze the problem are (1) religious theory, 2) drama turgi theory, 3) structural functional theory. The researchers did in qualitative research. The results showed (1) the form of transcendental communication in nyenuk. The non-verbal process includes all the symbols used in the implementation of the nyenuk ceremony, such as banten, uparengga, the color of the clothes used by panyenuk guests and the motions of the Sidhakarya mask dance. While the verbal process includes all processes that use words and language both orally and in writing, such as sipping panyenukan, stava puja and singing aunt Rangda (2) The transcendental communication function of nyenuk includes religious functions, repetition functions, substance functions and complementary functions, while substance functions transcendental communication nyenuk is to replace abstract components such as angels and bhagawan messengers of the gods, the complementary function of transcendental communication enjoyment is to complement the communication that occurs. (3) The meaning of the transcendental communication of nyenuk in the ngenteg linggih ceremony includes the theological meaning is an effort to make the earth a haven for the gods so as to create world peace, the sociological meaning is to build harmonious relationships among human beings, the ecological meaning is to protect the universe and its contents and the educational meaning . is to mature humans to become better individuals.